Implementasi Model Inkuiri Terbimbing Pada Peserta Didik Kelas 3 SD Negeri Jeron - Idam Ragil Widianto Atmojo; Fatimah Kusumarani (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of this study was to describe the implementation of the guided inquiry learning model for 3rd grade students at SD Negeri Jeron. This research method uses a descriptive qualitative approach. The implementation method in this research is divided into 2 stages, namely the observation stage and also the implementation stage of the guided inquiry model. The focus of this research is the application of guided inquiry learning models and science learning outcomes on the material properties of objects. The subjects of this study were teachers and students of grade 3 SD Negeri Jeron. This data collection technique is a test, observation and documentation with qualitative data analysis techniques, namely reducing data, presenting data, and drawing conclusions. The results of the study showed an increase in student learning outcomes from the first cycle with the sufficient category and increased to a good category in the second cycle. The conclusion of this study is that using the application of the guided inquiry learning model can make students active, learning becomes more meaningful and the science learning outcomes of 3rd grade students at SD Negeri Jeron increase.